Tooth replantation with adipose tissue stem cells and fibrin sealant: microscopic analysis of rat's teeth - YARAT, AYŞEN; AK, ESİN; AKYÜZ, SERAP HATİCE; TAPŞIN GÜLLÜOĞLU, SIDIKA; ÇETİNEL, ŞULE (SPRINGER INTERNATIONAL PUBLISHING AG, 2016)
Treatment for dental avulsion cases is early or late replantation of the traumatized teeth. Prognosis of the replanted tooth depends on the level of periodontal injury. Adipose tissue stem cells (ATSCs) were reported to improve periodontal ligament tissue (PDL) regeneration. Fibrin sealant (FS) contains thrombin and fibrinogen to form an adhesive fibrin clot routinely used in surgical procedures. Here, we aimed to investigate the effects of ATSCs + FS treatment on healing of PDL after tooth replantation in a rat model. After 60 min of extraction, maxillary central incisor teeth were replanted with ATSCs + FS. Two months later, the rats were sacrificed and hemimaxilla blocks were dissected out for histological analysis. The results showed that there was a significant improvement in histological findings of ATSCs + FS treated group compared to only FS treated and non-treated groups corresponding to reduced inflammatory resorption and increased new PDL formation. Furthermore, the ankylosis levels were lowered after ATSCs + FS treatment. Singular use of FS improved PDL healing moderately. Our results indicated that ATSCs + FS treatment improves PDL healing after tooth replantation suggesting a new therapeutic potential in the treatment of dental avulsion cases.
Keywords: Stem cells; Tooth avulsion; Tooth replantation; Fibrin tissue adhesive; Periodontal ligament; PERIODONTAL-LIGAMENT CELLS; PERMANENT INCISORS; STORAGE-CONDITIONS; HEALING-PROCESS; CLINICAL USE; EMDOGAIN((R)); THERAPY; DIFFERENTIATION; ANTIOXIDANT; MONKEYS